2022
DOI: 10.1007/s11356-022-18804-z
|View full text |Cite
|
Sign up to set email alerts
|

Green supply chain game model and contract design: risk neutrality vs. risk aversion

Abstract: This paper incorporates the players’ risk attitudes into a green supply chain (GSC) consisting of a supplier and a retailer. The supplier conducts production and determines the green level and wholesale price as a game leader; the retailer sells green products to consumers and determines the retail price as a follower. Equilibrium solutions are derived, and the influence of risk aversion on the GSC is examined. Our results show that, for the centralized GSC, risk aversion lowers the green level and the retail … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Also, researchers explored how to design an optimal cooperation format for the green supply chain to achieve coordination [ [52] , [53] , [54] , [55] , [56] ]. In addition, Cai et al [ 57 ] investigated green supply chain format design incorporating the player's risk attitudes and proposed that revenue sharing and cost sharing formats could coordinate the risk-neutral green supply chain. Xia and Niu [ 58 ] suggested that a manufacturer can design an appropriate format to maximize profit and implement environmental responsibilities if the retailer knows the extent of green-marketing efforts and true market size.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also, researchers explored how to design an optimal cooperation format for the green supply chain to achieve coordination [ [52] , [53] , [54] , [55] , [56] ]. In addition, Cai et al [ 57 ] investigated green supply chain format design incorporating the player's risk attitudes and proposed that revenue sharing and cost sharing formats could coordinate the risk-neutral green supply chain. Xia and Niu [ 58 ] suggested that a manufacturer can design an appropriate format to maximize profit and implement environmental responsibilities if the retailer knows the extent of green-marketing efforts and true market size.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Cao et al (2022) focused on the impact of manufacturer risk aversion on product green levels and pricing decisions, finding that manufacturer risk aversion increases retailer profits but decreases the greenness of the product. Cai et al (2022) established centralized and decentralized decision-making green supply chain models, analyzing the impact of member risk-averse characteristics on them. The study found that in a centralized supply chain, enterprise risk-averse behavior leads to decreases in product green levels and sale price, while in a decentralized supply chain, enterprise risk-averse behavior results in decreases in wholesale prices and sale price.…”
Section: Literaturementioning
confidence: 99%
“…In the fashion SSC, the manufacturer and the retailer sign a buy-back contract to solve the risk caused by the demand uncertainty of the retailer. Contracts can be more flexible in coordinating the distribution of profits among supply chain members and mitigate the effects of uncertainty (Cai et al 2022 ). Retailers in the clothing industry always hold many unsold products at the end of the sales season, which is one of the major risks of SSC, but a repurchase strategy can reduce the risk to retailers (Wang et al 2017 ).…”
Section: Logic Diagram Of Risk Management In Sustainable Supply Chainmentioning
confidence: 99%